American Medical Association complete guide to prevention and wellness (Wiley, 2008)
If you're one of the millions of people who have decided to take more direct control of their health by focusing on illness prevention and self-care, the American Medical Association Complete Guide to Prevention and Wellness is the resource you need. This authoritative guide provides valuable information to help you prevent disease and stay healthy throughout your life. It lays out the foundations of good health and shows you the basic steps you can take to reduce your health risks and prevent major illnesses such as heart disease, stroke, type 2 diabetes, high blood pressure, and some forms of cancer. You will learn how to avoid these and other common afflictions by making lifestyle changes and understanding what your body needs to stay fit and healthy